2008
DOI: 10.1002/tax.574019
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Agenda for Calcareous Dinoflagellate Research (Thoracosphaeraceae, Dinophyceae) including a nomenclatural synopsis of generic names

Abstract: Calcareous dinoflagellates are considered to be a monophyletic group of peridinoid taxa that have the potential to produce calcified exoskeletal structures during the life cycle, or that derive from such forms. Frequently, these calcareous bodies are excellently preserved in the fossil record and have received increased attention during the past three decades with regard to their use in biostratigraphy, climate and environmental reconstruction. Fossil and extant taxa have been classified in various, partly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 59 publications
0
39
1
Order By: Relevance
“…2004), vastly exceeding the diversity known from the today recognized species in the global oceans. Among myriad species of the Alveolata, the potential to produce calcareous structures is restricted to (i.e., has been considered apomorphic for) the Thoracosphaeraceae, arguing for the monophyly of this group (Wall and Dale 1968, Janofske 1992, Elbrächter et al. 2008).…”
mentioning
confidence: 99%
“…2004), vastly exceeding the diversity known from the today recognized species in the global oceans. Among myriad species of the Alveolata, the potential to produce calcareous structures is restricted to (i.e., has been considered apomorphic for) the Thoracosphaeraceae, arguing for the monophyly of this group (Wall and Dale 1968, Janofske 1992, Elbrächter et al. 2008).…”
mentioning
confidence: 99%
“…Fensome et al (1993) classified those species producing calcareous hypnozygotes as well as related ones in the subfamily Calciodinellaceae. Elbrächter et al (2008) proposed that the entirety of calcareous dinoflagellates, and non‐calcareous relatives derived from them, should be accommodated in a single family of the order Peridiniales, the Thoracosphaeraceae, combining the subfamily Calciodinelloideae and Thoracosphaerales, a separate dinoflagellate order. Phylogenetic analyses revealed that the potential to produce calcareous structures is apomorphic within alveolates, and non‐calcareous taxa nesting with calcareous dinoflagellates may have reduced calcification secondarily (Gottschling et al, 2005).…”
mentioning
confidence: 99%
“…Some genera and species of microfossils previously classified within the calcispheres have been assigned to the Dinophyceae (calcareous cysts of dinoflagellates) on the basis of definitive morphological criteria. Among these taxa are most of the genera listed by Elbrächter et al . (2008).…”
Section: Systematic Palaeontologymentioning
confidence: 99%